2015
DOI: 10.1155/2015/326802
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Hybrid and Elite Inbred Rice Varieties with respect to Their Source‐Sink Relationship

Abstract: Hybrid rice varieties have higher yield potential over inbred varieties. This improvement is not always translated to the grain yield and its physiological causes are still unclear. In order to clarify it, two field experiments were conducted including two popular indica hybrids (BRRI hybrid dhan2 and Heera2) and one elite inbred (BRRI dhan45) rice varieties. Leaf area index, chlorophyll status, and photosynthetic rate of flag leaf, postheading crop growth rate, shoot reserve translocation, source-sink relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
1
22
0
2
Order By: Relevance
“…found from a study that hybrid rice produced higher spikelets panicle -1 than inbred rice varieties. Similar type of results was also found from a study conducted by Haque et al (2015). They found that hybrids exhibited significantly lower number of panicles m -2 and on average 33.95% higher number of spikelets panicle -1 compared to the tested inbred.…”
Section: Percent Reduction In Weed Density and Biomasssupporting
confidence: 87%
“…found from a study that hybrid rice produced higher spikelets panicle -1 than inbred rice varieties. Similar type of results was also found from a study conducted by Haque et al (2015). They found that hybrids exhibited significantly lower number of panicles m -2 and on average 33.95% higher number of spikelets panicle -1 compared to the tested inbred.…”
Section: Percent Reduction In Weed Density and Biomasssupporting
confidence: 87%
“…Currently, it is believed that high yielding inbred varieties developed through conventional breeding have reached in yield plateau. Hybrid rice cultivars have a 15-30% yield advantage over modern inbred rice varieties, therefore, hybrid rice technology is considered as the key approach for increasing global rice production (Walker et al, 2008;Chauhan et al, 2011;Haque et al, 2015). It is also reported that even in weedy conditions, the yield of hybrid cultivars is high .…”
Section: Introductionmentioning
confidence: 99%
“…Grain yield of rice depends on the source-sink relationship (Zhao et al, 2006). Hybrid varieties have efficient capacity to supply assimilates to the grain from the source and the capacity of the sink to receive it fixes the higher yield than the inbred varieties (Haque et al, 2015). The number of unfilled grain increased in BRRI hybriddhan4 than the two inbred varieties.…”
Section: Hybrid Varieties Out-yielded the Inbredmentioning
confidence: 96%
“…Hybrid rice varieties have more photosynthesis capacity because of containing higher amount of chlorophyll in their leaf (Tang et al, 2010). In addition, flag leaf of hybrid rice contained more chlorophyll than the inbred rice genotypes which contributed to increase the photosynthesis capacity during panicle initiation (Haque et al, 2015). Higher photosynthesis potentiality of hybrid varieties attributed to accumulate higher amount of dry matter.…”
Section: Hybrid Varieties Out-yielded the Inbredmentioning
confidence: 99%
See 1 more Smart Citation